Data Altruism or Voluntary Data Sharing in the Economy - Jacolik, Magdalena (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
Along with technological progress, one can observe socio-economic changes taking place, and the transformation of the EU economy into a digital economy is an eloquent example. The scope of this transformation includes data, which plays an important role in the economy. This may be readily inferred from the European Strategy for Data published by the European Commission, which envisages a data-driven economy. The transformation towards a data-agile economy results in certain modification in the legal space. For instance, the proposal for a data governance regulation introduces an entity referred to as a data altruism organisation. The proposed act also requires EU Member States to designate a competent authority. This paper examines the functioning of said organisations and attempts to define their status, and discusses the duties of competent authorities which may possibly supervise the activities of data altruism organisations.